2012
DOI: 10.15376/biores.8.1.753-767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wood Acetylation with Vinyl Acetate and Acetic Anhydride on the Properties of Wood-Plastic Composites

Abstract: Chemical modifications of Scots pine (Pinus sylvestris) wood flour were performed with vinyl acetate (VA) and acetic anhydride (AA) in the presence of potassium carbonate as a catalyst. Scots pine wood flour samples were successfully acetylated with VA (19 wt% gain) and AA (24 wt% gain). The effect of chemical modification of the Scots pine wood flour with AA and VA on the mechanical properties of wood high-density polyethylene composites (WPC) was determined. It was observed that acetylation of wood flour all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 26 publications
(34 reference statements)
3
17
0
Order By: Relevance
“…The received signal can be written as in Equation (3), as a result of the combination of Equation (1) and Equation (2). In this research, the values of P t , G T , G R and d are available.…”
Section: Practical Antenna Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The received signal can be written as in Equation (3), as a result of the combination of Equation (1) and Equation (2). In this research, the values of P t , G T , G R and d are available.…”
Section: Practical Antenna Measurementsmentioning
confidence: 99%
“…The implementation of green technology especially on developing new material product will be an option to the industry and also the government in driving new economic growth by contributing to fiscal consolidation, enhancing productivity through greater efficiency in the use of natural and reusable resources [1][2][3][4]. Green technology product development, sustainability, cradle to cradle design and its viability are the major issues of this technology, whereby the product development can last indefinitely into the future without damaging or depleting natural resources, hence it can be fully reclaimed or reused [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors claim that acetylation improves the mechanical and thermal properties of WPCs (Tserki et al 2006;Lisperguer et al 2007;Abdul Khalil et al 2007;Özmen et al 2013). In contradiction to these studies, it was also reported that acetylation reduces the mechanical properties of WPCs (Luz et al 2008;Mat Taib et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the various lignocellulosics fibers such as flax, hemp, kenaf, corn stalks are attempted to use instead of wood flour as a substitute material in WPC. WPC can be produced by using various amounts of wood flour loading (about 50% or above) [3,5,[6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%